New Zealand Trustee Investing: Reflecting on Modern Portfolio Theory and the Ancient Distinction of Principal and Income - Manns Jr, F Philip (Victoria University of Wellington Law Review, 1998)
The New Zealand Trustee Amendment Act 1988 led the common law world in encouraging (perhaps requiring) trustees to use modern portfolio theory ("MPT") techniques when investing trust funds. A recent High Court decision essentially held that trustees should have engaged in MPT-based investment since 1972. Full integration of MPT principles into trust law affects many areas of trust administration, perhaps most prominently the ancient distinction of principal and income. In addition, renewed attention to careful drafting of a settler’s investment and pay out intentions and greater investment diversification are likely consequences of MPT-based trust investing.